Discovery of Highly Potent Dual Orexin Receptor Antagonists via a Scaffold‐Hopping Approach. (8th July 2016) - Heidmann, Bibia; Gatfield, John; Roch, Catherine; Treiber, Alexander; Tortoioli, Simone; Brotschi, Christine; Williams, Jodi T.; Bolli, Martin H.; Abele, Stefan; Sifferlen, Thierry; Jenck, François; Boss, Christoph
Abstract: Starting from suvorexant (trade name Belsomra), we successfully identified interesting templates leading to potent dual orexin receptor antagonists (DORAs) via a scaffold‐hopping approach. Structure–activity relationship optimization allowed us not only to improve the antagonistic potency on both orexin 1 and orexin 2 receptors (Ox1 and Ox2, respectively), but also to increase metabolic stability in human liver microsomes (HLM), decrease time‐dependent inhibition of cytochrome P450 (CYP) 3A4, and decrease P‐glycoprotein (Pgp)‐mediated efflux. Compound80 c [{(1 S, 6 R )‐3‐(6, 7‐difluoroquinoxalin‐2‐yl)‐3, 8‐diazabicyclo[4.2.0]octan‐8‐yl}(4‐methyl‐[1, 1′‐biphenyl]‐2‐yl)methanone] is a potent and selective DORA that inhibits the stimulating effects of orexin peptides OXA and OXB at both Ox1 and Ox2. In calcium‐release assays, 80 c was found to exhibit an insurmountable antagonistic profile at both Ox1 and Ox2, while displaying a sleep‐promoting effect in rat and dog models, similar to that of the benchmark compound suvorexant. Abstract : Scaffold hopping for hits : Dual orexin receptor antagonism has been shown to be a new mechanism for the treatment of primary insomnia and other sleep‐related disorders. We report a scaffold‐hopping approach as a powerful tool to identify high‐quality hits as well as the structural optimization of one scaffold into80 c, a potent and orally bioavailable brain‐penetrant dual orexin receptor antagonist.